Study on the growth and spatial distribution of the root system of different european pear cultivars on quince rootstock combinations Estudo do crescimento e distribuição espacial do sistema radicular de diferentes combinações de cultivares de pereiras europeias sobre porta-enxertos de marmeleiros - Machado B.D. (2018)
© 2018, Sociedade Brasileira de Fruticultura. All rights reserved.Information on root development is an essential tool capable of identifying, among plants of a species, the one that has the greatest capacity to potentiate growth and development characteristics in its aerial part. The aim of this study was to characterize the distribution of the root system throughout the soil profile of different European pear cultivars and quince rootstock combinations on medium plant density systems (2500 plants ha-1). The combinations evaluated were: Abbè Fetel/Adams, Clapp’s Favourite/EMA, Santa Maria/Adams, Rocha/Adams, Decana du Comice/Adams, Packham’s Triumph/EMA, Packham’s Triumph/Adams and Conference/Adams. In relation to effective depth, it was observed that up to 40 cm deep, 80% of the total root length and 83% of root concentration were found for all combinations. For the effective distance, it was observed that 80% of the total root length is distributed in up to 80 cm for all combinations, except for Clapp’s Favourite/EMA, whose actual distance was 100 cm. It was observed that the average of six combinations, 86% of root growth in the horizontal distance is located up to 80 cm.